Strategi Komunikasi Persuasif Pencegahan Bullying Pada Siswa Di Smk Pesantren Terpadu Mojokerto - Firdaus, Achmad (Philosophiamundi, 2023)
Bullying behavior, which can also be called intimidating, involves attacking people physically, verbally, and psychologically by individuals or groups who are stronger than those who are weaker. In the school environment that is under the auspices of Islamic Boarding Schools, bullying is still encountered. This, of course, will have a negative impact on school activities for victims of bullying. Schools already have a strategy for handling bullying cases for their students in an effort to prevent acts of bullying, but the results are not efficient enough. So the researchers took the title Persuasive Communication Strategy for Prevention of Studentsâ€™ Bullying at SMK Pesantren Terpadu Mojokerto. With the formulation of the problem under study, namely "How is a Persuasive Communication Strategy to Prevent Bullying in Students at SMK Pesantren Terpadu Mojokerto?â€ which aims to analyze persuasive communication strategies carried out by counselors at SMK Pesantren Terpadu Mojokerto in an effort to prevent bullying, The researcher uses a qualitative descriptive method because it will describe a persuasive communication strategy to prevent bullying among students at SMK Pesantren Terpadu Mojokerto in detail. The conclusions from the results of the study are: a) The association technique is in the form of inserting bullying material at the morning assembly and when teaching and learning activities; b) Integration techniques, namely by approaching students both verbally and non-verbally; c) The reward technique is by giving punishment to the perpetrators of bullying and giving appreciation to students who dare to report bullying cases; d) The arrangement technique is by using the Javanese language when conveying messages to students; and e) The red-herring technique, namely by intermediary for students who are victims and perpetrators of bullying and provide solutions for bullying behavior that arises so that bullying can be overcome and minimized. The strategy that is considered the most suitable to be implemented at SMK Pesantren Terpadu Mojokerto as an effort to prevent bullying is a persuasive communication strategy with Arrangement and Red-herring techniques.